Financial Factors Contribution to SMEs’ Profitability - Esy Nur Aisyah; Ana Khabibatul Umami (Universitas Hayam Wuruk Perbanas, 2022)
Micro, small, and medium enterprises play a very important role in driving the economy both nationally and internationally. The level of profitability is one indicator of the performance of SMEs. One of the factors that affect profitability is the financial factor. Therefore, this study attempts to analyze the contribution of financial factors (Own Capital, Loan Capital, Assets, Trade Credit, Production Costs, Sales, Average Wages, Taxes, and Lagged Profitability) to the profitability of SMEs. The population consists of all SMEs in the city of Malang. The sampling technique used an iteration formula and obtained a sample of 116 SMEs in Malang that received financing from Islamic financial institutions, banks, and non-banks. Questionnaires and observational interviews collected data. The data analysis technique used Multiple Linear Regression. The result of the determination test on this research model is 0.839 (84%). And based on the results of the partial test, of the nine independent variables in the study, only three variables have a significant positive effect on the profitability of SMEs, namely Own Capital, Loan Capital, and Lagged Profitability. And of the three variables that provide the largest contribution or influence on profitability is Own Capital.